A strange tribute to Taylor Swift [compact disc]. - Currie, Cherie, 1959-; Tiffany; Cole, Samantha; Lewis, Linda Gail; Harvey, Danny B.; Seauphine, Sammy B.; Connor, Joanna; Kristina, Sonja; K4tey
A diverse collection of musical icons from across the genre spectrum completely revamp the songs of country/pop goddess, Taylor Swift!